Best Practices in Designing Extended Matching Questions for Evaluating Higher Order Cognitive Skills in Medical Education (Bangladesh Journal of Medical Science, 2025)
Applying best practices in designing extended matching questions (EMQs) is fundamental for accurately assessing the higher order cognitive skills of medical students. EMQs, when wellconstructed, can evaluate critical thinking, clinical reasoning, and decision-making skills, which are vital in the medical field. Prioritizing clarity, relevance, and complexity in question design, educators can create assessments that align more closely with real-world medical problemsolving. Implementing these strategies is a key step towards uplifting the standards of medical education. This paper offers a comprehensive guide in designing high quality EMQs that test higher order cognitive skills of medical students, aiming to promote best assessment practices in medical education and uphold high standards of student evaluation.Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 58-66